2021
DOI: 10.1093/plphys/kiab034
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and ecological warnings that dodders pose an exigent threat to farmlands in Eastern Africa

Abstract: Invasive holoparasitic plants of the genus Cuscuta (dodder) threaten African ecosystems due to their rapid spread and attack on various host plant species. Most Cuscuta species cannot photosynthesize and hence rely on host plants for nourishment. After attachment through a peg-like organ called a haustorium, the parasites deprive hosts of water and nutrients, which negatively affects host growth and development. Despite their rapid spread in Africa, dodders have attracted limited research attention, although d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…may be enormous and unpredictable. For example, C. reflexa is an emerging threat to tea, coffee, and mango production in Eastern Africa [ 16 ], C. campestris is a well-known pest on sugar beet in many European countries [ 17 ], and C. gronovii is damaging cranberry production in North America [ 18 ]. Yield losses may reach 50–70% of the expected [ 19 , 20 ], and the quality of the yield may be also negatively affected [ 21 ].…”
Section: Parasitic Plants and Agriculturementioning
confidence: 99%
“…may be enormous and unpredictable. For example, C. reflexa is an emerging threat to tea, coffee, and mango production in Eastern Africa [ 16 ], C. campestris is a well-known pest on sugar beet in many European countries [ 17 ], and C. gronovii is damaging cranberry production in North America [ 18 ]. Yield losses may reach 50–70% of the expected [ 19 , 20 ], and the quality of the yield may be also negatively affected [ 21 ].…”
Section: Parasitic Plants and Agriculturementioning
confidence: 99%
“…Their intimate physiological connection with their often closely related host and, in some cases, resilient seed banks, make it challenging to manage infestations (Benvenuti et al, 2005; Parker, 2012; Vurro et al, 2017). Increased concerns in a context of global change foster the need of refining predictive models to guide conservation of endangered species and pest control (Cai et al, 2022; Masanga et al, 2021; Ren et al, 2020). While successful parasitism critically depends on efficient host location, evidence has accumulated that parasitic plants can evaluate the quality of available hosts and ‘choose’ which ones they parasitise (Li et al, 2023; Marquardt & Pennings, 2010; Sandner & Matthies, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Their intimate physiological connection with their often closely related host and, in some cases, resilient seed banks, make it challenging to manage infestations (Benvenuti et al, 2005;Parker, 2012;Vurro et al, 2017). Increased concerns in a context of global change foster the need of refining predictive models to guide conservation of endangered species and pest control (Cai et al, 2022;Masanga et al, 2021;Ren et al, 2020).…”
mentioning
confidence: 99%
“…Moreover, resistant hosts, including sweet potato and tomato, can produce degrading enzymes in cell walls and inhibit the penetration of haustorium into plant tissues [3]. Masanga et al [40] found that Mangifera indica successfully mounted a post-attachment resistance response to dodder. In summary, in direct contact with haustoria, epidermal tomato cells elongate and die following a hypersensitive response, whereas a secondarily modified tissue is formed in the hypodermis to protect against haustoria penetration [23].…”
Section: Introductionmentioning
confidence: 99%